The Effectiveness of Short Card Game Method on Primary Students’ Learning Outcomes - Ratnasari, Khurin; Melinda, Vannisa Aviana; Fadholi, Amak; Masuwd, Mowafg Abrahem (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
Mathematics learning in elementary school has an important role in building students' logical and analytical thinking skills. However, there are still many students who have difficulty in understanding basic math concepts. One of the factors causing this is the teaching method that is less interesting and tends to be monotonous, so that students are less motivated to actively learn. To overcome this problem, this study aims to evaluate the effectiveness of the Short Card game method on students' math learning outcomes. In this study, there is a lack of application of interactive and fun learning methods in teaching mathematics at the elementary school level. Although various innovative teaching methods have been introduced, the application of Short Card games in the context of mathematics learning is still limited, especially regarding their effect on improving student learning outcomes. This study used a type of pre experimental designs with a one group pretest-posttest research form. The results showed that the Short Card game method had a significant positive effect on students' math learning outcomes. Students who learned using this method showed a higher increase in learning outcomes compared to students who used conventional methods. Thus, the Short Card game proved to be effective in improving learning outcomes.